Psychiatric inpatients' views of their mental health, and their experience of social change, during the pandemic: A report from Qatar. Issue 3 (9th December 2021) - Badanapurkar, Ashishkumar; Nelson, Deborah; Alabdulla, Majid; Reagu, Shuja; Woodruff, Peter; Varghese, Sejo; Aly, Shereen Mohammed; Haddad, Peter M.
Accessible Summary: What is known on the subject?: There is only limited information on how the COVID‐19 pandemic has affected people diagnosed with mental health disorders, especially people admitted to psychiatric wards. We surveyed the views of inpatients at Qatar's only psychiatric hospital regarding how the pandemic had affected their mental health and social changes they had experienced during the pandemic. What the paper adds to existing knowledge?: Nearly half (43%) of those who completed the survey reported that the pandemic had led to a deterioration in their mental health. Those who reported deterioration in their mental health during the pandemic were significantly more likely to have experienced negative social changes during the pandemic. Examples included increased stress from the home and reduced ability to discuss emotions/feelings with family members. What are the implications for practice?: Mental health services need to ensure ongoing support for patients during and after the pandemic. Mental health nurses have a pivotal role including identifying early warning signs of relapse of mental disorders, delivering talking treatments and providing practical advice and COVID‐19‐related education. Further work is needed to assess the views of people diagnosed with mental health problems in different countries and at a different time point during the pandemic. Abstract: Introduction: The impact of the COVID‐19 pandemic on people under the care of mental health services has received relatively little attention in the scientific literature. Aim: To assess psychiatric inpatients' views regarding their mental health and experience of social change during the pandemic. Method: Cross‐sectional survey of consecutive patients admitted to Qatar's only psychiatric hospital between mid‐June and mid‐October 2020. Results: Data were analysed for 114/284 (40%) patients admitted during the study period. 8 (7%) reported a history of COVID‐19. 43% reported that the pandemic had led to deterioration in their mental health, 11% to an improvement and 39% that there had been no attributable change. Those reporting worsened mental health, attributable to the pandemic, were significantly more likely to report having experienced four negative social changes during the pandemic, namely reduced ability to discuss emotions/feelings with family members, decreased time spent exercising, decreased time spent relaxing and increased stress from the home. Demographic factors did not distinguish those reporting worsened mental health from those whose mental health was improved or unchanged. Discussion: A large proportion of psychiatric inpatients reported negative social and mental health changes during the pandemic. However, the study cannot determine causality. Implications for practice: Mental health services should consider the psychological and social aspects of people's lives, including their interactions with family, friends and the community. This is especially relevant during the COVID‐19 pandemic due to its wide impact on society. Interventions for people diagnosed with mental health disorders should address their psychological and social needs.